2013
DOI: 10.1103/physrevb.88.214506
|View full text |Cite
|
Sign up to set email alerts
|

Muon spin relaxation and electron/neutron diffraction studies of BaTi2(As1xSbx

Abstract: We present the results of muon spin relaxation/rotation, transmission electron microscopy, and neutron diffraction measurements performed on several specimens of BaTi 2 (As 1−x Sb x ) 2 O, which is known to have either charge density or spin density wave ordering at T DW for all x, and superconductivity below T c ≈ 1 K for x = 1. Zero-field muon spin relaxation measurements show no significant increase in relaxation rate at the density wave ordering temperature for any composition, indicating that the density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
38
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 25 publications
4
38
1
Order By: Relevance
“…The possibility of SDW formation in BaTi 2 (As,Sb) 2 O, either commensurate or incommensurate, was subsequently ruled out by muon spin relaxation and 121/123 Sb nuclear resonance measurements, which show conclusively that no magnetic order develops at any temperature probed 26,27,31 . On the other hand, a conventional CDW should be evident through an associated structural distortion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The possibility of SDW formation in BaTi 2 (As,Sb) 2 O, either commensurate or incommensurate, was subsequently ruled out by muon spin relaxation and 121/123 Sb nuclear resonance measurements, which show conclusively that no magnetic order develops at any temperature probed 26,27,31 . On the other hand, a conventional CDW should be evident through an associated structural distortion.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a conventional CDW should be evident through an associated structural distortion. However, initial electron and neutron diffraction studies on the Sb endmember 26 found no broken symmetry or any signature of superlattice formation at low temperatures, nor was a CDW gap formation observed in angle-resolved photoemission measurements of the nested Fermi surfaces (although a slight depression of the density of states at other momenta was found to correlate in temperature with the resistivity anomaly 35 ). The possibility of an incommensurate CDW was also ruled out by 121/123 Sb nuclear resonance measurements 31 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations